Accidental Electric Shock during Pregnancy: Reflection on a Case - Johnny Awwad; Antoine Hannoun; Farah Fares; Ghina Ghazeeri (Thieme Medical Publishers, Inc., 2013)
Abstract Objectives Data on fetal effects following accidental electric shock during pregnancy are scarce. We report on a case of accidental maternal electric shock associated with benign fetal arrhythmia in a woman at 28 weeks' gestation. Study Design Case report. Results Although electrocution involving low-voltage, low-frequency current has been associated with fatal cardiac arrhythmias and conduction abnormalities, two protective parameters in the present case likely reduced the fetal injury: the dry skin at the site of current entry and the hand-to-hand pathway of current flow. Conclusion Because the pathophysiology of electric injury is altered during pregnancy, assessment of fetal well-being should be prompted no matter how trivial an incident may appear.